Предмет:
МатематикаАвтор:
анонимУпростим заданное выражение.
√20 - √3 * (√15 - √12) = √4 * √5 - √3 * √15 - √3 * (-√12) = √22 * √5 - √(3 * 15) + √(3 * 12) = 2√5 - √45 + √36 = 2√5 - √(9 * 5) + √62 = 2√5 - √9 * √5 + 6 = 2√5 - √32 * √5 + 6 = 2√5 - 3√5 + 6 = -√5 + 6 = 6 - √5.
Ответ: 6 - √5.
Автор:
milagroscohenДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть